Ocupação antrópica e sócio-ambiental na área de captação do reservatório do DNOS Santa Maria- RS. - Goldani, Jurandi Zanoti (2006)
The present research has as objective accomplishes a study of the environmental impact provoked by the anthropic progress on the native vegetation, in order to identify the permanent preservation areas (PPA) like hillsides of hills, ciliary's forests and ofter subsidies for its preservation.The more intense man's intervention in the environment through the natural resources, especially forests, rivers and areas of permanent preservation are a consequence of the technological progress and the population growth that we have been verifying along the time. These natural resources for turning more and more important to the human being besides the destruction of yours forests, will do in a elose future, with that the treatment of the water has a high price too much for many. For better understanding of the research, it was elaborated thematic maps as: Geomorfologic, Hydrologic, Hipsometric, Downward slope, Use of the earth x steepness <5% and >47% in two periods, 1995 and 2003, with the purpose to know the space and environmental transformations in this interval of time and to propose solutions of softening the found environmental impacts. Parallel through interview it was verified vary irregularities as: I spill of garbage in the margins of rivers and along highways, sewer spilled to open sky and deforestation, irregular occupations forming small slums. In the rising economical partner it was detected that 31% of the garbage are collected twice a week and 66% only once a week. The ones that deposit the garbage to open sky add 62% and the one that burn add 28%. About the sewers, 25% spill it at open sky without any treatment or channeled towards the rivers, of these interviewees 45% produce some type of environmental impact. Of the homes of the catchment 87% they possess property registration, 13% are invaded lots, and ali of them are in the Cechela's hillside.